(untitled) (Journal of Biochemistry, Microbiology and Biotechnology, 2025)
Bacterial cellulose (BC) is an eco-friendly biopolymer with unique properties, including high purity, mechanical strength, and biocompatibility. Its production is influenced by fermentation conditions such as carbon sources (e.g., sucrose, glucose), nutrient composition, temperature (25-32 °C), pH (4.0-7.5), and aeration. Static cultivation yields highly crystalline BC with layered structures, while agitated systems enhance productivity but reduce mechanical integrity. Process optimization using waste-derived substrates (e.g., molasses, fruit residues) and statistical modeling (e.g., RSM) improves cost efficiency and sustainability. BC’s nanofibrillar structure provides exceptional tensile strength (200-300 MPa), high water retention (up to 98%), and thermal stability (decomposition at 300-350 °C). These properties make it valuable in biomedical applications (wound dressings, tissue engineering), food packaging (edible films), and industrial uses (nanocomposites, filtration membranes). However, scaling up production faces challenges, including genetic instability in continuous cultures, shear stress in bioreactors, and high downstream processing costs. Recent advancements focus on metabolic engineering, hybrid fermentation systems, and immobilized cell techniques to enhance yield and scalability. BC’s potential as a sustainable alternative to synthetic materials is promising, particularly in medicine and green manufacturing. However, overcoming production cost and yield limitations remains critical for broader industrial adoption. Future research should optimize strain-specific fermentation, integrate circular bioeconomy principles, and refine functionalization techniques to expand BC’s commercial applications.